Rapidly identifying bioactive compounds from Zhisou oral liquid by immobilized receptor‐based high‐performance affinity chromatography. Issue 17 (11th July 2021) - Fu, Xiaoying; Zhao, Xue; Zheng, Xinxin; Wang, Taotao; Shayiranbieke, Aerduosi; Li, Linkang; Cao, Fang; Ren, Jianping; Li, Qian; Zhao, Xinfeng
Abstract: The identification of bioactive compounds in complex matrices remains a major challenge due to the lack of highly efficient and specific methods. This work developed an approach based on high‐performance affinity chromatography to identify the potential antitussive compounds from Zhisou oral liquid . The main methods include the synthesis of immobilized beta2‐adrenoceptor by a one‐step method, the screening and identification of the potential bioactive compounds by the receptor column coupled with mass spectrometry, and the binding mechanism analysis of the compounds to the receptor by the in vivo experiment, injection amount dependent method and molecular simulation. We identified the potential bioactive compounds of Zhisou oral liquid as glycyrrhizic acid, platycodin D, tuberostemonine, and hesperidin. In vivo experiment showed that the combinational utilization of the four compounds was possible to present an equivalent antitussive effect to the formula. The docking results demonstrated that hydrogen bonds and Van der Waals forces were the main forces to drive the binding of the four compounds to beta2‐adrenoceptor. We concluded that the four compounds are the effective components in Zhisou oral liquid. The proposed strategy is possible to provide an alternative for the development of highly efficient methods to pursue the bioactive compounds of complex matrices.